Establishment of cheap and reliable real-time PCR for quantitation of HIV-1 viral load in plasma - Supadej,K. (Medical Association of Thailand, 2015)
Objective: To establish an inexpensive and reliable real-time PCR for quantitation of HIV-1 RNA from plasma samples. Material and Method: Previously analyzed 145 HIV-1 positive plasma samples with viral load ranging from less than 40 to approximately 1,000,000 copies/ml were included in the present study. HIV-1 gag gene was amplified and cloned into TA cloning vector. External standard curve was plotted using in vitro transcribed HIV-1 RNA and utilized for viral quantitation in the samples. Scramble nucleotides located in HIV-1 specific probe was subsequently constructed and used for individual systemic control. The correlation coefficient and Bland-Altman plot were applied for statistical analysis of the two methods. Results: The limit of quantitation of the validated assay was 31 copies/ml and the linear range was approximate 31-1 × 107 copies/ml. After reproducibility determination using intra-and inter-run assay, it was implied that the coefficient of variation (%CV) was significantly increased while the low copy number of RNA was examined. A highly correlation (r2 = 0.8099) and good agreement were obtained when the two assays were compared. Conclusion: Developed real-time PCR was inexpensive and reliable for quantitation of HIV-1 viral load in plasma.